Z source based switched capacitor nine level boost inverter with a modified modulation strategy - Ahmed R. Hasouna; Sabry A. Mahmoud; Awad E. El-Sabbe; Dina S. M. Osheba (Scientific Reports)
Abstract This article presents a Z source (ZS) based switched capacitor multilevel inverter (SC-MLI) with low capacitors charging inrush currents utilizing a modified modulation strategy. The topology generates nine output voltage levels with quadruple voltage gain utilizing eight power switches, five capacitors, two inductors, four discrete diodes, and a single DC source. The voltage gain can be further increased by applying shoot through (ST) states to the frontend ZS-network. Owing to its high voltage gain, the topology is suitable for low voltage renewable energy sources such as photovoltaics (PV), and fuel cells (FC). A modified modulation strategy is presented based on the conventional level shifted sinusoidal pulse width modulation (LS-SPWM). The proposed modulation strategy improves the dc-link utilization at higher modulation index. A detailed mathematical analysis is provided for the gain calculation based on the modified modulation strategy. A comparative study is implemented to verify the merits of the proposed topology. A simulation model is implemented utilizing MATLAB / Simulink to verify the topology characteristics. The power losses and efficiency calculations are presented using Altair PSIM. Furthermore, an experimental prototype is constructed to verify the simulation findings. The topology is tested with different loading conditions at numerous modulation index values and ST duty ratios. Furthermore, step change conditions are implemented to test the topology response. The effect of the ZS network on the switched capacitors charging inrush currents is validated. The proposed topology shows an overall advantage in terms of the output characteristics as well as the hardware requirements.